Monitoring of pH and temperature effects in fermentation process of itaconic acid - Siti Rozaimah, Sheikh Abdullah, Dr.; Jamaliah, Md. Jahim; Norliza, Abd. Rahman; Norhayati, Ismail; Idayu, S. M.; Saleha, Atan (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/